Methodologies and Behaviour of Self-Healing Phenomena in Cementitious Composites: A Review - Rasha Jasim Al Karawi; Merool Vakil; Seyed Sina Mousavi (Journal of Engineering and Sustainable Development)
Despite the extended lifespan of concrete structures under ideal circumstances, the service life is significantly reduced due to the cracks created by various loads. Unwanted crack treatments are effective only on the exterior side of the accessible concrete constructions. Therefore, there is a great need to incorporate a self-healing (S-H) mechanism within the concrete matrix. This review discusses a general trend in developing S-H concrete in the construction industry. It consists of two parts: Part I introduces an overview of S-H concrete by describing the basic concepts and available S-H techniques (agents/materials) and analyzing their applications, critiques, and performance in various published studies. Part II critically discusses the conceptual life cycle cost, the maturity level of S-H concrete, the commercial situation, potential applications, field behavior, and challenges to be addressed in future years. The most important outcome of this review is a deeper understanding of the self-healing phenomenon and its potential applications. It is shown that self-healing technologies can give concrete power to heal and prepare itself, which reduces the need for regular maintenance, substantial cost savings, and environmental protection.